APPLICATIONS OF GRAPH COLORING METODS FOR DETERMINING THE MINIMUM NUMBER OF STAGES LIGHT CONTROLLED INTERSECTIONS (Perner's Contacts, 2011)
The article discusses possible approaches to solving the problem to find the minimum number of phases required to drive light controlled intersections. The introductory chapters are described and discussed approaches (heuristic and exact), which can be used to solve the problem. In the next chapter, these approaches are applied to obtain solutions at the real intersection, and final chapter compares the advantages and disadvantages of using different approaches.
Keywords: intersection; phase; traffic flow; graph; node